2020
DOI: 10.1021/acs.orglett.0c01745
|View full text |Cite
|
Sign up to set email alerts
|

Urea-Catalyzed Vinyl Carbocation Formation Enables Mild Functionalization of Unactivated C–H Bonds

Abstract: Herein we report the 3,5bistrifluoromethylphenyl urea-catalyzed functionalization of unactivated C-H bonds. In this system, the urea catalyst mediates the formation of high-energy vinyl carbocations that undergo facile C-H insertion and Friedel-Crafts reactions. We introduce a new paradigm for these privileged scaffolds where the combination of hydrogen bonding motifs and strong bases affords highly active Lewis acid catalysts capable of ionizing strong C-O bonds. Despite the highly Lewis acidic nature of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…However, high intrinsic kinetic barrier arising from sp 2 ‐C↔ sp ‐C rehybridization makes the formation of vinyl cations sluggish [3] . Recently, a major breakthrough in overcoming the high intrinsic kinetic barrier was achieved by using catalysts containing weakly coordinating anions (WCAs) such as [Et 3 Si][HCB 11 Cl 11 ] (Figure 1a), [4] Li[Al(OC(CF 3 ) 3 ) 4 ], [5] [Ph 3 C][B(C 6 F 5 ) 4 ] [6] and Li[Urea] [7] . The role of WCAs is to enhance the Lewis acidity of the cations to abstract the leaving group X − , as well as to stabilize the generated vinyl cation intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…However, high intrinsic kinetic barrier arising from sp 2 ‐C↔ sp ‐C rehybridization makes the formation of vinyl cations sluggish [3] . Recently, a major breakthrough in overcoming the high intrinsic kinetic barrier was achieved by using catalysts containing weakly coordinating anions (WCAs) such as [Et 3 Si][HCB 11 Cl 11 ] (Figure 1a), [4] Li[Al(OC(CF 3 ) 3 ) 4 ], [5] [Ph 3 C][B(C 6 F 5 ) 4 ] [6] and Li[Urea] [7] . The role of WCAs is to enhance the Lewis acidity of the cations to abstract the leaving group X − , as well as to stabilize the generated vinyl cation intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…R f = 0.33 (cyclohexane/EtOAc, 90:10). 33 Following GP1 performed with SMAHO 1c (131 mg, 0.75 mmol, 1.5 equiv) and p-toluoyl chloride (2c; 66 L, 0.5 mmol, 1.0 equiv), the desired product was obtained after purification by flash chromatography [silica gel, 50 mL, cyclohexane/EtOAc, 95:5 (250 mL), 90:10 (250 mL)] as a colorless oil; yield: 112 mg (90%). R f = 0.37 (cyclohexane/EtOAc, 90:10).…”
Section: Compound 5bcmentioning
confidence: 99%
“…It was found that various functional groups could be compatible with the system, such as pinacol boronic ester, chloro, bromo, and iodo, which were unreactive under previously reported silylium conditions. A shortcome of the In an effort to extend the range of catalysts for these fascinating transformations, the same group recently discovered 3,5-bistrifluoromethylphenyl ureas, common hydrogenbonding motifs, could catalyze C-H insertion reactions of vinyl triflates 16 under basic conditions (Scheme 6) [17]. Highly active lithiated urea catalyst, which could ionize strong C-O bonds and abstract triflate from sp 2 carbons, were generated from the combination of ureas and strong bases.…”
Section: Ionization Of Vinyl Triflatesmentioning
confidence: 99%